Edukasi Penggunaan Kosmetik pada Remaja di Pondok Khusus Putri Al-Halimy Lombok Barat - Puspitasari, Candra Eka; Mukhlisah, Neneng Rachmalia Izzatul; Ridwan, Sucilawaty; Pratiwi, Eskarani Tri; Manafe, Deary Pretty Genovani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Cosmetics are pharmaceutical preparations intended for external use and are classified based on their ingredients and functions. Given their widespread use across all age groups, from infancy to the elderly, cosmetics are currently widely utilized by adolescents. Adolescents represent a vulnerable group to exposure to illegal or unsafe cosmetic products due to their natural curiosity and tendency to experiment with new things. Therefore, the objective of this community-based activity was to improve adolescents’ knowledge regarding safe cosmetics and their appropriate use. This activity was conducted at Pondok Khusus Putri Al-Halimy, West Lombok Regency, involving all students of MTs (Islamic junior high school) and MA (Islamic senior high school), as well as teaching staff. The program was carried out smoothly and received positive enthusiasm from participants. The educational intervention was effective in increasing students’ knowledge about cosmetic use. Furthermore, based on evaluation using questionnaires to assess respondents’ knowledge levels, it was found that the educational exposure successfully enhanced participants’ understanding. Knowledge regarding general knowledge about cosmetic use among adolescents increased by 3%, while illegal cosmetics increased by 9.13%